Implementasi Nilai-Nilai Demokrasi pada UKM Unit Kegiatan Kerohanian Islam Universitas Negeri Surabaya - Nahdliyatul Islamiyah; Muhammad Turhan Yani (Universitas Negeri Surabaya (Unesa), 2023)
This study aims to determine the implementation of democracy in the Student Activity Unit of the Islamic Spiritual Activity Unit, State University of Surabaya. In this organization not only examines the religion of Islam but also applies the values ​​of democracy applied in the Indonesian state. Democracy implies the meaning of power which is essentially the people who hold the highest mandate in democracy. The essence of democracy is of the people, by the people and for the people. Judging from the meaning of the word democracy, it is clear that the people play an important role. However, in practice it can be understood and implemented differently, even development is very uncontrolled. In the UKKI UNESA organization, it should be in line with the values ​​that exist in democracy and the creation of freedom and deliberation to reach consensus. The research method used is qualitative. Data collection techniques used are interviews, observation, and documentation. Informants in this study were the general chairman, functionaries, and members. The conclusion of this study is that the implementation of democratic values ​​in the organization of the Islamic Spiritual Activity Unit is in line with the principles of Pancasila democratic values ​​which refers to Cipto's theory in journal (Aulawi, A., & Srinawati : 2019), although it is not perfect yet. The results of this study are expected to be useful and contribute to balancing thoughts on the application of democratic values ​​and can add to the treasures of thoughts for writers and readers in general regarding democratic values. Keyword: Democracy, Organization, Discussion